The way I heard it - Rowe, Mike, 1962- (Gallery Books, 2019)
"Emmy-award winning gadfly Mike Rowe presents a ridiculously entertaining, seriously fascinating collection of his favorite episodes from America's #1 short-form podcast, The Way I Heard It, along with a host of memories, ruminations, illustrations, and insights. It's a delightful collection of mysteries. A mosaic. A memoir. A charming, surprising must-read"--